(untitled) (Journal of Asian Development Studies, 2025)
This study examines factors behind the perpetuation of undemocratic military rule in a democratic country, Pakistan, by the character of Zia ul Haq in Muhammad’s Hanif’s novel A Case of Exploding Mangoes (2008). This research further demonstrates how Zia ul Haq uses soft power to mold people’s social behavior and mindset in Hanif’s novel. This study employs a non-empirical method to analyze the research query under the theoretical groundwork of Antonio Gramsci’s theory of cultural hegemony (1929–1935) that he gave in Prison Notebooks. The use of civil society has been highlighted in this research as a means to manufacture the masses’ consent and rule over them by General Zia-Ul-Haq’s regime. Close reading and textual analysis methods have been applied to interpret the chosen novel. The research examines the regime of General Zia-ul-Haq and how social institutions are manipulated to subdue Pakistanis and avoid their insurgency against the undemocratic military dictatorship. For data collection, the researcher probes into the novel and reviews related articles and previous research papers. This paper examines how Muhammad Hanif dismantles the alternative facts about General Zia’s reign and Pakistan’s history. This paper contributes to dismantling power dynamics in society and concealing injustice. Post-analysis results reveal that ideology and media have been specifically exploited during Zia ul Haq’s reign to shape the mindset of the public and get their consent to his undemocratic regime. Islamization of the state was done to get the consent of the masses. Media and press were biased and were working to portray a positive image of Zia’s regime.